Preoperative Anaemia and Associated Postoperative Outcomes in Noncardiac Surgery Patients in Central Region of Ghana - Gladys Amponsah; Alice Charwudzi (Anesthesiology Research and Practice)
Introduction. Several studies suggest that preoperative anaemia (PA) is associated with adverse postoperative outcomes, but little is known about these outcomes in the Central Region of Ghana. This study aims to determine the prevalence of PA among noncardiac surgical patients and its implications for their postoperative outcomes. Methods. This study was designed as an observational study; data including demographics and clinical and laboratory results were collected from the patients’ records and through interviews. Results. A total of 893 inpatient surgical cases undergoing elective and emergency operations, aged 15 years and above with mean age of 44.2 ± 17.0 yrs, were enrolled. The prevalence of PA was 54.3%, mostly microcytic with or without hypochromia (57.2%). The prevalence was higher in females than males (p≤0.001). Preoperative anaemia was significantly associated with prolonged length of hospital stay (OR: 2.12 (95% CI: 1.49–3.10)). Allogeneic blood transfusion significantly prolonged the length of hospital stay (OR 4.48 (95% CI: 2.67–7.51)). 15.5% of the anaemic patients received oral iron supplements compared to 2.2% of nonanaemic patients (p≤0.001). Conclusion. Preoperative anaemia is common among noncardiac surgical patients. It is independently and significantly associated with prolonged hospital stay leading to the use of increased healthcare resources. It is also the main predictor for perioperative allogeneic blood transfusions and the use of haematinics.